Influenza Immunizations in the Elderly: A Continuous Quality Improvement Project - Juma, A.; Evans, M. F.; Bloom, J. (Methods of Information in Medicine, 2000)
As part of the continuous quality improvement program at The Toronto Hospital’s Department of Family & Community Medicine (TTH-DFCM), it was considered necessary to examine the structures, processes and outcomes of influenza immunization for the elderly. Objective: The study sought to (a) document the current influenza immunization process; (b) quantify influenza immunization rates for elderly patients during two consecutive immunization seasons (1996 and 1997), and compare these rates across physician teams, attending staff vs. residents, patient gender, and patient age groups; (c) compare influenza immunization rates with other centers; and (d) identify barriers and propose solutions to improve influenza immunization rates in the elderly. Design: Evaluation Formative Research. Setting: A computerized roster of 15,000 patients at The Toronto Hospital, Department of Family and Community Medicine, a University of Toronto academic teaching center. Participants: Active patients age 65 years and over. Dependent variable: Influenza immunization. Independent variables: Physician Teams, Physician status, Patient gender, and Patient age group. Results: Immunization rates of attendees increased from 75.4% to 78.7%; over 3% increase from 1996 to 1997. Major subgroups which benefited from increased immunization rates were patients in the Blue team, patients age 70-74 years, and female patients. Conclusion: This study presents a rigorous examination of the components of the influenza immunization program, and demonstrates improved immunization rates over a two-year period. Suggestions for future action have been identified. The study design can also serve as a model for future clinical quality improvement projects.
Keywords: Influenza; Immunization; Elderly; Quality Management; Quality Improvement